Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.21018/rjcpr.2016.1.204
|View full text |Cite
|
Sign up to set email alerts
|

Humor, Loneliness and Interpersonal Communication: A Quantitative Study of Romanian Older Adults

Abstract: <p>This quantitative study examines the correlations between humor, loneliness, gender and aging by presenting the results from a sample of eighty-three older Romanian adults, aged sixty and above. The first section of the paper is a comprehensive review of the social-psychological literature on aging, gender and humor. The second section assesses the findings generated from a study that uses the Multidimensional Sense of Humor Scale (Thorson &amp; Powell, 1993) and the Social and Emotional Lonelines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 32 publications
(47 reference statements)
0
14
1
1
Order By: Relevance
“…The current study departs from the study by Schiau (2016) that found the use of humor in interpersonal communication to be correlated with a reduced sense of social loneliness in a sample of Romanian older adults. Humor can function as a coping mechanism, helping individuals adapt to various situations and difficulties, across the age groups, and there are indicators in the literature that humor is experienced and valued differently at different ages.…”
Section: Introductioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The current study departs from the study by Schiau (2016) that found the use of humor in interpersonal communication to be correlated with a reduced sense of social loneliness in a sample of Romanian older adults. Humor can function as a coping mechanism, helping individuals adapt to various situations and difficulties, across the age groups, and there are indicators in the literature that humor is experienced and valued differently at different ages.…”
Section: Introductioncontrasting
confidence: 99%
“…A principal components factor analysis was conducted, and produced four dimensions. However, items loaded differently on the four factors than they did in the original English language instrument (Thorson & Powell, 1993), and also differently from the sample of Romanian older adults (Schiau, 2016), suggesting an age-specific difference in the way humor is used and assessed. not used in the current study.…”
Section: Measures and Validationmentioning
confidence: 68%
See 2 more Smart Citations
“…Así, Martin 15 conceptualiza el humor en base a un conjunto de características como 1) la capacidad para comprender chistes y otros estímulos humorísticos, 2) la expresión de humor y alegría, 3) la capacidad de realizar comentarios graciosos, 4) la apreciación de diversos tipos de bromas u otros materiales cómicos, 5) la búsqueda activa de fuentes que provocan risa, 6) el recordar chistes y anécdotas divertidas en la vida y, finalmente, 7) la tendencia a usar el humor como mecanismo de afrontamiento. En relación a esta última característica, estudios recientes 16 indican que el humor puede actuar como un mecanismo de afrontamiento ante las dificultades aparecidas durante la vejez. Esto proporciona a los adultos mayores la capacidad de cambiar el pensamiento y recuperar una sensación de control, permitiéndoles a su vez adaptarse a los cambios físicos, cognitivos y sociales característicos de esta etapa del ciclo vital 17 .…”
Section: Revista Española De Geriatría Y Gerontologíaunclassified